Physicochemical, Mineral, and Sensory Properties of Masuku (Uapaca kirkiana) Beverages - Ali, Benson; Chunda, Maria (University of Sultan Ageng Tirtayasa, 2023)
Masuku (Uapaca Kirkiana) are wild fruits that are in abundance from December to March. Masuku are highly perishable fruits hence they have to be processed into other products to extend their shelf life. The main objective of this study was to determine the physiochemical, nutritional, and sensory properties of the masuku juices. Two formulations of masuku juice were prepared, one batch involved peeling the masuku and obtaining the pulp, while in the other batch, they were not peeled. The masuku were just washed and squeezed to obtain the pulp. The resulting pulp was used for juice processing. The juices were analyzed for physiochemical and mineral properties. Themasuku fruit had high pH content than that recommended for juice making and juice from unpeeled masuku was more acidic than juice from peeled masuku. Juice from unpeeled Masuku had high magnesium content as compared to juice from peeled masuku. While on paired preference test, the results showed that there was a significant difference in preference between the two batches (p<0.05) where the juice from peeled Masuku was most preferred over the juice from unpeeled masuku. In conclusion, masuku raw pulp acid content should be balanced with additional acids when making juices. Masuku juice can be used as a rich source of magnesium and zinc. There are traces of magnesium in the skin of masuku fruits hence squeezing the whole fruit when pulping can help to utilize the fruit fully.